Physical growth and nutritional status of adolescent students - Cossio Bolaños, Wilbert (2014)
Objectives: To determine physical growth parameters and to assess nutritional status of school adolescents. Design: Descriptive comparative study. Institution: Liceo Naval Admiral Lizardo Montero, Lima, Peru. Participants: Adolescents aged 12-15 years. Interventions: A non-probability selection of 501 school children of both sexes (251 men and 250 women) was done. Variables determined included weight and height. Mean, standard deviation, percentages, t-test for independent samples and paired (p <0.05) and chi-square (p<0.05) analysis were done. Main outcome measures: Variables of growth and nutritional status. Results: Compared to international references, there were no significant differences (p <0.05) in weight and height by sex in adolescents. The nutritional status showed higher proportion of well nourished subjects (74.5% in men and 75.6% in women) compared with low birth weight (2% in men, 0.8% in women), overweight (16.3% in men and 20.4 in women) and obesity (7.2% in men and 3.2% in women). Conclusions: Physical growth pattern was similar to international reference values but the high prevalence of overweight in both sexes suggests a public health problem.